Los procesos cognitivos básicos de atención, memoria y comprensión lectora en estudiantes de primer ciclo de la carrera de Psicopedagogía, de la Facultad de la Educación, el Arte y la Comunicación de la Universidad Nacional de Loja, 2024. - Sarango Pinza, Dalinda Elizabeth (2024)
The general objective of this study was to analyze the relationship between the levels of basic cognitive processes of attention and memory and reading comprehension in first-year students of Psychopedagogy at the Faculty of Education, Art, and Communication of the Universidad Nacional de Loja. The study adopted a mixed, descriptive, correlational, and cross-sectional approach. The sample was formed by 37 students, aged between 18 and 29 years. The instruments used were the D2 attention test, the RIAS subscale for memory, and the ICLAU for reading comprehension. The results showed that 82.85% of the students have a low level of attention, 51.52% of them obtained a high level of memory, and the 75.76% reached a medium level of reading comprehension. To determine the correlation, Kendall's Tau-b correlation coefficient was applied, which determined a value of 0.36 for the correlation between attention and comprehension, that is within a range of +0.11 to +0.50, establishing a positive correlation of medium magnitude between attention and reading comprehension. Similarly, for memory and reading comprehension, a value of 0.50 was found, also within the range of +0.11 to +0.50, indicating a positive correlation of a medium magnitude between memory and reading comprehension. Finally, it is concluded that there is a medium positive correlation between attention, memory, and reading comprehension.